Resin composition, resin sheet, resin sheet with conductor layer, laminated substrate, and method for producing resin sheet
By adding a resin composition of inorganic filler within a specific range to the liquid crystal polymer, the molding problem and pollution problems are solved by melt extrusion method, and the dielectric characteristics and safety are improved.
Patent Information
- Application Number
- CN202380039791.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-01
- Filing Date
- 2023-06-13
- Publication Date
- 2024-12-24
AI Technical Summary
During the forming process, the liquid crystal polymer sheet has low melt tension due to the presence of the filler material, making it difficult to form into a sheet, and foreign matter contamination may occur in traditional methods.
The resin composition containing liquid crystal polymer and inorganic filler is shaped by melt extrusion to ensure that the specific surface area, maximum diameter and content of the inorganic filler are within a specific range to increase the melt tension and avoid contamination.
The resin composition formed into a sheet by melt extrusion is realized, which improves dielectric characteristics and heat dissipation, reduces the risk of pollution, and enhances the high-frequency region dielectric characteristics of the laminated substrate and the safety of electronic equipment.
Smart Images

Figure CN119183468A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition, a resin sheet, a resin sheet with a conductor layer, a laminated substrate, and a method for producing a resin sheet. Background Art
[0002] Patent Document 1 discloses a resin composition characterized in that (A) a synthetic resin having a melting temperature of 300° C. or higher contains (B) a plate-shaped inorganic filler having the following properties, namely, water dispersion pH: 5.5 to 8.0, eluted alkali amount Na: 30 ppm or less, K: 40 ppm or less, maximum diameter a: 50 μm or less, thickness b: 1.0 μm or less, and aspect ratio (a / b): 20 or more. Patent Document 1 discloses a liquid crystal polymer as a specific example of a synthetic resin having a melting temperature of 300° C. or higher.
[0003] Patent document 2 discloses a liquid crystalline polyester resin composition, which contains (B) 10 to 80 parts by weight of a plate-like filler relative to 100 parts by weight of (A) a liquid crystalline polyester resin, wherein the melting point of the liquid crystalline polyester resin in the liquid crystalline polyester resin composition is 300° C. or higher and lower than 330° C., and a molded article formed by molding the liquid crystalline polyester resin composition has a load deflection temperature measured in accordance with ASTM D648 of 260° C. or higher and lower than 285° C.
[0004] Patent document 3 discloses a manufacturing method for manufacturing a liquid crystal polymer film containing a filler, which is characterized in that it includes the following steps: obtaining a mixed powder of a liquid crystal polymer and a filler; forming a laminate having a layer of the mixed powder between two thin film-like heat-resistant substrates; and heating and compressing the laminate between a pair of heating rollers.
[0005] Prior Art Literature
[0006] Patent Literature
[0007] Patent document 1: International Publication No. 01 / 40380
[0008] Patent Document 2: Japanese Patent Application Publication No. 2016-89154
[0009] Patent Document 3: Japanese Patent Application Publication No. 2014-111699 Summary of the invention
[0010] Problem that the invention aims to solve
[0011] Liquid crystal polymer sheets have low dielectric constants and are therefore known as members for improving dielectric properties in high frequency regions of laminated substrates used in various electronic devices. On the other hand, thinning of the liquid crystal polymer sheets is required in order to reduce the thickness of the laminated substrates.
[0012] In view of this, the present inventors have studied forming a resin composition containing a liquid crystal polymer into a sheet shape by a melt extrusion method in order to obtain a thin liquid crystal polymer sheet.
[0013] However, the present inventors have found through research that if the resin composition containing a liquid crystal polymer and a filler (filler) described in Patent Documents 1 and 2 is formed into a sheet by melt extrusion, the melt tension of the resin composition is low due to the presence of the filler, and therefore the resin composition breaks during the forming process, resulting in difficulty in forming into a sheet.
[0014] Furthermore, the present inventors have found through research that, if a resin composition containing a liquid crystal polymer and a filler is to be formed into a sheet by the method described in Patent Document 3, although it is possible to form the resin composition into a sheet, in the middle of the process, since there is a step of kneading the molten liquid crystal polymer and the filler and then crushing them, so there is a so-called contamination that foreign matter (for example, metal) generated by the crusher used in this step is mixed into the obtained liquid crystal polymer sheet.
[0015] The present invention is completed in order to solve the above-mentioned problems, and its purpose is to provide a resin composition that can be formed into a sheet by a melt extrusion method. In addition, the purpose of the present invention is to provide a resin sheet comprising the above-mentioned resin composition, a resin sheet with a conductor layer having the above-mentioned resin sheet, and a laminated substrate having the above-mentioned resin sheet with a conductor layer. Furthermore, the purpose of the present invention is to provide a method for manufacturing a resin sheet that can form a resin composition into a sheet by a melt extrusion method without causing pollution.
[0016] Technical solutions to solve problems
[0017] The resin composition of the present invention is characterized in that it contains a liquid crystal polymer and an inorganic filler, wherein the specific surface area of the inorganic filler is 30 m 2 / cm 3 Hereinafter, the maximum diameter of the inorganic filler is 100 μm or less, and the content of the inorganic filler is 0.1 vol % or more and 60 vol % or less.
[0018] The resin sheet of the present invention is characterized by comprising the resin composition of the present invention.
[0019] The resin sheet with a conductor layer of the present invention is characterized by comprising the resin sheet of the present invention and a conductor layer adjacent to at least one main surface side of the resin sheet.
[0020] The laminated substrate of the present invention is characterized by comprising the resin sheet with a conductor layer of the present invention.
[0021] The method for producing a resin sheet of the present invention is characterized by comprising the steps of: preparing a resin composition comprising a liquid crystal polymer and a 2 / cm 3 An inorganic filler having a maximum diameter of 100 μm or less and a maximum diameter of 100 μm or less, wherein the content of the inorganic filler is 0.1 vol % or more and 60 vol % or less; and forming the resin composition into a sheet by melt extrusion.
[0022] Effects of the Invention
[0023] According to the present invention, a resin composition that can be formed into a sheet by a melt extrusion method can be provided. In addition, according to the present invention, a resin sheet comprising the above-mentioned resin composition, a resin sheet with a conductor layer having the above-mentioned resin sheet, and a laminated substrate having the above-mentioned resin sheet with a conductor layer can be provided. Furthermore, according to the present invention, a method for manufacturing a resin sheet that can form a resin composition into a sheet by a melt extrusion method without causing pollution can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a schematic cross-sectional view showing an example of the resin sheet of the present invention.
[0025] Figure 2 is an example of the resin sheet of the present invention, and is a diagram showing Figure 1 Schematic cross-sectional views of different examples.
[0026] Figure 3 is an example of the resin sheet of the present invention, and is a diagram showing Figure 1 and Figure 2 Schematic cross-sectional views of different examples.
[0027] Figure 4 This is a schematic cross-sectional view showing an example of the resin sheet with a conductor layer of the present invention.
[0028] Figure 5 It is a schematic cross-sectional view showing an example of the laminated substrate of the present invention.
[0029] Figure 6 This is a schematic cross-sectional view showing a step of preparing a resin sheet with a conductor layer in one example of the method for producing a laminated substrate of the present invention.
[0030] Figure 7 This is a schematic cross-sectional view showing a step of preparing a resin sheet with a conductor layer in one example of the method for producing a laminated substrate of the present invention.
[0031] Figure 8 This is a schematic cross-sectional view showing a step of preparing a resin sheet with a conductor layer in one example of the method for producing a laminated substrate of the present invention.
[0032] Fig. 9 This is a schematic cross-sectional view showing a step of forming a via hole in one example of the method for manufacturing a laminated substrate of the present invention.
[0033] Fig.10 This is a schematic cross-sectional view showing a step of forming a via hole in one example of the method for manufacturing a laminated substrate of the present invention.
[0034] Fig.11 This is a schematic cross-sectional view showing a step of filling a conductive paste in an example of the method for producing a laminated substrate of the present invention.
[0035] Fig.12 This is a schematic cross-sectional view showing a step of filling a conductive paste in an example of the method for producing a laminated substrate of the present invention.
[0036] Fig.13 This is a schematic cross-sectional view showing a step of forming an interlayer connection conductor in one example of the method for manufacturing a laminated substrate according to the present invention. DETAILED DESCRIPTION
[0037] Hereinafter, the resin composition of the present invention, the resin sheet of the present invention, the resin sheet with a conductor layer of the present invention, the laminated substrate of the present invention, and the method for manufacturing the resin sheet of the present invention are described. It should be noted that the present invention is not limited to the following structures, and can also be appropriately changed within the scope of the present invention. In addition, the structure obtained by combining multiple preferred structures described below also belongs to the present invention.
[0038] The resin composition of the present invention is characterized in that it contains a liquid crystal polymer and an inorganic filler, wherein the specific surface area of the inorganic filler is 30 m 2 / cm 3 Hereinafter, the maximum diameter of the inorganic filler is 100 μm or less, and the content of the inorganic filler is 0.1 vol % or more and 60 vol % or less.
[0039] The resin composition of the present invention comprises a liquid crystal polymer and an inorganic filler.
[0040] The resin composition of the present invention can make the dielectric constant of the resin sheet including the resin composition of the present invention lower by containing a liquid crystal polymer. Therefore, the resin composition of the present invention can improve the dielectric properties in the high frequency region of the laminated substrate having the resin sheet including the resin composition of the present invention.
[0041] In the resin composition of the present invention, it is preferred that the liquid crystal polymer comprises a copolymer of p-hydroxybenzoic acid (HBA) and 6-hydroxy-2-naphthoic acid (HNA).
[0042] The copolymer of p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid is generally referred to as a type II fully aromatic polyester (also referred to as a type 1.5 fully aromatic polyester). Type II fully aromatic polyesters are less susceptible to hydrolysis than type III partially aromatic polyesters and are therefore preferred as constituent materials for laminated substrates. In addition, type II fully aromatic polyesters have a small dielectric loss tangent because they are derived from naphthalene rings, and therefore contribute to reducing electrical energy loss in the resin sheet in the laminated substrate.
[0043] In the resin composition of the present invention, the liquid crystal polymer may contain type I wholly aromatic polyester, type III partially aromatic polyester, or type I wholly aromatic polyester and type III partially aromatic polyester in addition to type II wholly aromatic polyester.
[0044] The structure (type) of each monomer constituting the liquid crystal polymer can be analyzed by reactive pyrolysis gas chromatography-mass spectrometry (reactive pyrolysis GC-MS method).
[0045] In the resin composition of the present invention, when the liquid crystal polymer includes a copolymer of p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid, it is preferred that the molar ratio of p-hydroxybenzoic acid to 6-hydroxy-2-naphthoic acid is 0.20 or more and 5 or less.
[0046] In the liquid crystal polymer, when the molar ratio of p-hydroxybenzoic acid to 6-hydroxy-2-naphthoic acid is less than 0.20 or more than 5, the melting point of the resin composition may be higher than the preferred range described below.
[0047] In the resin composition of the present invention, it is preferred that when the liquid crystal polymer contains a copolymer of p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid, when the total amount of monomers is set to 100 mol %, the liquid crystal polymer contains 10 mol % or more of p-hydroxybenzoic acid and 10 mol % or more of 6-hydroxy-2-naphthoic acid.
[0048] When the content ratio of each monomer of p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid in the liquid crystal polymer is smaller than 10 mol%, it is sometimes difficult to achieve the liquid crystal properties of the liquid crystal polymer, the melting point of the resin composition is within the preferred range described later, and the dielectric loss tangent of the liquid crystal polymer is reduced.
[0049] The ratio and content of each monomer constituting the liquid crystal polymer can be analyzed by reactive pyrolysis gas chromatography-mass spectrometry.
[0050] The resin composition of the present invention contains a liquid crystal polymer as a resin component. The resin component only needs to contain a liquid crystal polymer as a main component, and may contain components other than the liquid crystal polymer.
[0051] In this specification, the main component refers to the component with the highest weight percentage.
[0052] The resin composition of the present invention can impart the following various properties to the resin sheet including the resin composition of the present invention by containing an inorganic filler.
[0053] The resin composition of the present invention can also impart heat dissipation to the resin sheet by including an inorganic filler. When the resin sheet has heat dissipation, the heat generated by the internal resistance of the component is easily dissipated to the outside, so the safety and reliability of the laminated substrate having the resin sheet and the electronic device using the laminated substrate are easily improved.
[0054] Examples of the inorganic filler capable of imparting heat dissipation include boron nitride, aluminum nitride, silicon carbide, alumina, talc, and metals. Among them, boron nitride is preferred as the inorganic filler capable of imparting heat dissipation because it does not easily decompose the liquid crystal polymer.
[0055] The resin composition of the present invention can also impart a higher dielectric constant to the resin sheet by including an inorganic filler. When the resin sheet has a higher dielectric constant, when a laminated substrate having the resin sheet is used for an antenna component, the radio waves used by the antenna component are easily shortened, and therefore the antenna component is easily miniaturized.
[0056] Examples of the inorganic filler capable of imparting a high dielectric constant include titanium oxide, barium titanate, calcium titanate, zinc zirconate titanate, etc. Among them, titanium oxide is preferred as the inorganic filler capable of imparting a high dielectric constant because it does not easily decompose the liquid crystal polymer.
[0057] The resin composition of the present invention can also impart magnetism to the resin sheet by including an inorganic filler. When the resin sheet has magnetism, in a laminate substrate having the resin sheet, electromagnetic waves from the outside can be shielded by the resin sheet (noise absorption).
[0058] Examples of the inorganic filler capable of imparting magnetism include ferrites and metals. Among them, ferrites are preferred as the inorganic filler capable of imparting magnetism because they are less likely to undergo changes in physical properties due to oxidation.
[0059] The resin composition of the present invention can also impart flame retardancy to the resin sheet by containing an inorganic filler. When the resin sheet has flame retardancy, the safety of the laminated substrate having the resin sheet and further the electronic device using the laminated substrate is easily improved.
[0060] Examples of the inorganic filler capable of imparting flame retardancy include magnesium hydroxide, antimony oxide, aluminum hydroxide, zinc borate, molybdate compounds, tin oxide compounds, phosphorus compounds, iron oxide, cuprous oxide, silicon dioxide, etc. Among them, magnesium hydroxide is preferred because it has a greater effect of imparting flame retardancy.
[0061] The resin composition of the present invention may also contain a lightweight inorganic filler. When the inorganic filler in the resin composition is lightweight, the resin sheet is lightweight, and therefore, when the laminated substrate having the resin sheet is used for automobile parts, the fuel efficiency of the automobile is easily improved.
[0062] Examples of the inorganic filler that can reduce weight include inorganic fillers having a hollow structure, such as hollow silica, hollow glass, etc. Among them, hollow silica is preferably used as the inorganic filler that can reduce weight because it does not easily decompose the liquid crystal polymer.
[0063] In the resin combination of the present invention, the inorganic filler can also be subjected to surface treatment. That is, in the resin combination of the present invention, a surface treatment layer can also be provided on the surface of the inorganic filler. Thus, the dispersibility of the inorganic filler in the resin combination is easily improved, and therefore, the physical property of the resin combination derived from the inorganic filler is not easy to produce deviation according to the position in the resin combination.
[0064] Examples of the constituent material of the surface treatment layer include silane coupling agents, titanate coupling agents, phosphoric acid esters, and fatty acids (eg, stearic acid, oleic acid, etc.).
[0065] In the resin composition of the present invention, the specific surface area of the inorganic filler is 30 m 2 / cm 3 the following.
[0066] In the resin composition of the present invention, the specific surface area of the inorganic filler is as small as 30 m 2 / cm 3 Below, the specific surface area ratio of inorganic filler is 30m 2 / cm 3 Compared with a resin composition with a large surface area, the intermolecular interaction and entanglement of the liquid crystal polymers are likely to remain, so the melt tension of the resin composition is not easily reduced. That is, the resin composition of the present invention has a specific surface area as small as 30 m 2 / cm 3 Hereinafter, it is easy to maintain a higher melt tension. Therefore, when the resin composition of the present invention is formed into a sheet by a melt extrusion method, the resin composition can withstand the tensile stress in the forming process. Therefore, the resin composition of the present invention is not easy to break in the forming process of being formed into a sheet by a melt extrusion method.
[0067] In the resin composition of the present invention, it is preferred that the specific surface area of the inorganic filler is 20 m 2 / cm 3 the following.
[0068] In the resin composition of the present invention, the specific surface area of the inorganic filler is 20m 2 / cm 3 Then, the interface between the liquid crystal polymer and the inorganic filler is likely to decrease, and therefore the amount of moisture captured at the interface between the liquid crystal polymer and the inorganic filler is reduced, and as a result, the water absorption rate of the resin sheet including the resin composition is likely to decrease.
[0069] In the resin composition of the present invention, it is preferred that the specific surface area of the inorganic filler is 0.1 m 2 / cm 3 above.
[0070] In the resin composition of the present invention, when the specific surface area of the inorganic filler is less than 0.1 m 2 / cm 3 When the maximum diameter of the inorganic filler described later is 100 μm or less, it may be difficult to do so.
[0071] The method for determining the specific surface area of the inorganic filler according to the state of the resin composition is as follows. First, after taking out the inorganic filler from the resin composition, the inorganic filler is degassed. Afterwards, the specific surface area of the inorganic filler is measured by the BET1 point method. Specifically, the specific surface area of the inorganic filler is calculated based on the amount of nitrogen adsorbed on the surface of the inorganic filler weighed to a degree of more than 0.1g and less than 1.0g. When measuring the specific surface area of the inorganic filler, for example, a specific surface area measuring device such as "Macsorb (registered trademark)", a fully automatic specific surface area measuring device made by Mountech, is used. It should be noted that when determining the specific surface area of the inorganic filler according to the state of the resin sheet or laminated substrate described later, after taking out the inorganic filler from the resin sheet of the object, the specific surface area of the inorganic filler is determined by the above method.
[0072] In the resin composition of the present invention, the maximum diameter of the inorganic filler is 100 μm or less.
[0073] In the resin composition of the present invention, the maximum diameter of the inorganic filler is reduced to less than 100 μm. Compared with a resin composition in which the maximum diameter of the inorganic filler is greater than 100 μm, when the resin composition is formed into a sheet by melt extrusion, the obtained resin sheet is less likely to have holes, and therefore, the resin sheet is less likely to break.
[0074] In the resin composition of the present invention, it is preferred that the maximum diameter of the inorganic filler is 1 μm or more.
[0075] In the resin composition of the present invention, when the maximum diameter of the inorganic filler is less than 1 μm, it may be difficult to make the specific surface area of the inorganic filler to be 30 m 2 / cm 3 the following.
[0076] The method for determining the maximum diameter of the inorganic filler according to the state of the resin composition is as follows. First, after taking out the inorganic filler from the resin composition, the inorganic filler is ultrasonically dispersed in ethanol. Afterwards, the particle size distribution of the inorganic filler is measured by the laser diffraction / scattering method. At this time, the particle size of the inorganic filler is measured as the equivalent circle diameter. When measuring the particle size distribution of the inorganic filler, for example, a laser diffraction / scattering particle size distribution measuring device such as the laser diffraction / scattering particle size distribution measuring device "LA-960" made by Horiba Manufacturing Co., Ltd. is used. Then, the maximum particle size in the particle size distribution of the obtained inorganic filler is determined as the maximum diameter of the inorganic filler. It should be noted that when determining the maximum diameter of the inorganic filler according to the state of the resin sheet or laminated substrate described later, after taking out the inorganic filler from the resin sheet of the object, the maximum diameter of the inorganic filler is determined by the above method.
[0077] In the resin composition of the present invention, the content of the inorganic filler is 0.1 vol % or more and 60 vol % or less.
[0078] In the resin composition of the present invention, the content of the inorganic filler is more than 0.1vol% and less than 60vol%, and the melt tension of the resin composition is not easy to reduce. That is, in the resin composition of the present invention, the content of the inorganic filler is more than 0.1vol% and less than 60vol%, it is easy to maintain a higher melt tension, and it is easy to show the characteristics given by the above-mentioned inorganic filler. Therefore, when the resin composition of the present invention is formed into a sheet by a melt extrusion method, the resin composition can withstand the tensile stress in the forming process. Therefore, the resin composition of the present invention is not easy to break in the forming process of being formed into a sheet by a melt extrusion method.
[0079] In the resin composition of the present invention, when the content of the inorganic filler is less than 0.1 vol%, the above-mentioned properties imparted by the inorganic filler are not easily manifested. In the resin composition of the present invention, even if the content of the inorganic filler is as low as 0.1 vol%, for example, flame retardancy can be imparted to the resin sheet.
[0080] In the resin composition of the present invention, when the content of the inorganic filler exceeds 60 vol %, the melt tension of the resin composition tends to decrease, and thus the resin composition tends to break during the molding process of molding into a sheet by melt extrusion.
[0081] The method for determining the content of inorganic filler according to the state of the resin composition is as follows. First, using a thermogravimetric / differential thermal simultaneous determination (TG-DTA) device, the resin composition is heated to 600°C, for example, and then placed at 600°C for 45 minutes, thereby completely thermally decomposing the resin component (liquid crystal polymer, etc.) in the resin composition. Then, the content of the inorganic filler in the resin composition is calculated based on the volume (weight) of the inorganic filler remaining after the resin component is removed. It should be noted that when the content of the inorganic filler is determined according to the state of the resin sheet or laminated substrate described later, in the above method, the measurement object can be changed from the resin composition to the resin sheet.
[0082] In view of the above, according to the resin composition of the present invention, even in a composite state containing a liquid crystal polymer and an inorganic filler, by satisfying all the specific surface areas of the inorganic fillers of 30 m 2 / cm 3 A resin composition that can be formed into a sheet by a melt extrusion method can be achieved even if the maximum diameter of the inorganic filler is 100 μm or less and the content of the inorganic filler is 0.1 vol % or more and 60 vol % or less.
[0083] In the resin composition of the present invention, the inorganic filler is preferably in a plate-like shape.
[0084] Generally, in a resin composition in a composite state including a liquid crystal polymer and an inorganic filler, the orientation of the liquid crystal polymer is easily reduced due to the presence of the inorganic filler, and therefore, when the resin composition is formed into a sheet to form a resin sheet, the tensile elongation at break of the resin sheet is easily reduced. In contrast, when the inorganic filler is plate-shaped, the orientation of the liquid crystal polymer in the resin composition is not easily reduced, and therefore, when the resin composition is formed into a sheet to form a resin sheet, the tensile elongation at break of the resin sheet is not easily reduced.
[0085] In this specification, the plate-like shape refers to a shape that expands in the in-plane direction perpendicular to the thickness direction, such as boron nitride and talc.
[0086] In addition, in the resin composition of the present invention, the inorganic filler may be in a shape other than a plate shape, for example, a spherical shape.
[0087] In the resin composition of the present invention, it is preferred that the average particle size of the inorganic filler is 0.1 μm or more and 30 μm or less.
[0088] The method for determining the average particle size of the inorganic filler according to the state of the resin composition is as follows. First, the particle size distribution of the inorganic filler obtained when determining the maximum diameter of the inorganic filler is converted into a particle size distribution represented by cumulative probability, thereby obtaining the volume-based cumulative particle size distribution of the inorganic filler. Then, the median particle size D is obtained based on the obtained volume-based cumulative particle size distribution of the inorganic filler. 50 (particle size when the cumulative probability becomes 50%), the median particle size D 50 When the average particle size of the inorganic filler is determined based on the state of the resin sheet or laminate substrate described later, the average particle size of the inorganic filler is determined by the above method after the inorganic filler is removed from the target resin sheet.
[0089] In the resin composition of the present invention, it is preferred that the thickness of the inorganic filler is 1 nm or more and 1000 nm or less.
[0090] The method for determining the thickness of the inorganic filler according to the state of the resin composition is as follows. First, after taking out the inorganic filler from the resin composition, an image of the inorganic filler is taken by a scanning electron microscope (SEM). Next, the image of the obtained inorganic filler is subjected to image analysis by analysis software, etc., thereby measuring the size of the inorganic filler in the short side direction (the direction with the shortest size). Then, 100 inorganic fillers are subjected to the above-mentioned size measurement in the short side direction, and the average value of the 100 measured values obtained is determined as the thickness of the inorganic filler. It should be noted that when the thickness of the inorganic filler is determined according to the state of the resin sheet or laminated substrate described later, the thickness of the inorganic filler is determined by the above-mentioned method after the inorganic filler is taken out from the resin sheet of the object.
[0091] In the resin composition of the present invention, it is preferred that the aspect ratio of the inorganic filler is 2 or more and 100 or less.
[0092] The method for determining the aspect ratio of the inorganic filler according to the state of the resin composition is as follows. First, after taking out the inorganic filler from the resin composition, the image of the inorganic filler is taken by a scanning electron microscope. Next, the image of the obtained inorganic filler is subjected to image analysis by analysis software, thereby measuring the size in the short side direction of the inorganic filler and the size in the long side direction (the longest direction of the size) of the inorganic filler. Then, 100 inorganic fillers are subjected to the above-mentioned dimension measurement in the short side direction and the long side direction, and the average value of 100 measured values obtained as the size in the short side direction is set to A, and the average value of 100 measured values obtained as the size in the long side direction is set to B, and B / A at this time is determined as the aspect ratio of the inorganic filler. It should be noted that when determining the aspect ratio of the inorganic filler according to the state of the resin sheet or laminated substrate described later, after taking out the inorganic filler from the resin sheet of the object, the aspect ratio of the inorganic filler is determined by the above-mentioned method.
[0093] In the resin composition of the present invention, it is preferred that the average particle size of the inorganic filler is 0.1 μm to 30 μm, the thickness of the inorganic filler is 1 nm to 1000 nm, and the aspect ratio of the inorganic filler is 2 to 100.
[0094] In the resin composition of the present invention, by satisfying all the conditions that the average particle size of the inorganic filler is 0.1 μm or more and 30 μm or less, the thickness of the inorganic filler is 1 nm or more and 1000 nm or less, and the aspect ratio of the inorganic filler is 2 or more and 100 or less, the liquid crystal polymer is easily captured by the inorganic filler, and therefore, when the resin composition is formed into a sheet to form a resin sheet, the linear expansion coefficient in the in-plane direction of the resin sheet is easily reduced. When the linear expansion coefficient in the in-plane direction of the resin sheet is small, when the resin sheet with a conductor layer or a laminated substrate described later is formed using the resin sheet, the linear expansion coefficient in the in-plane direction of the resin sheet can be made close to the linear expansion coefficient in the in-plane direction of the conductor layer (for example, copper foil). As a result, in the resin sheet with a conductor layer or the laminated substrate, warping caused by the difference in the linear expansion coefficient in the in-plane direction of the resin sheet and the conductor layer is not easy to occur.
[0095] In the resin composition of the present invention, it is preferred that the melt tension at a temperature 20° C. higher than the melting point of the resin composition is 1.0 mN or more.
[0096] The resin composition of the present invention has a melt tension of 1.0 mN or more at a temperature 20° C. higher than the melting point of the resin composition, and thus can be easily formed into a sheet by a melt extrusion method.
[0097] In the resin composition of the present invention, it is preferred that the melt tension at a temperature 20° C. higher than the melting point of the resin composition is 7.0 mN or less.
[0098] In the resin composition of the present invention, when the melt tension at a temperature 20°C higher than the melting point of the resin composition is higher than 7.0 mN, it is required to increase the tension when pulling the molded product in the process of forming the resin composition into a sheet by melt extrusion. When the tension when pulling the molded product is increased in this way, it is difficult to keep the speed when pulling the molded product constant, so the thickness of the obtained resin sheet sometimes varies.
[0099] The melting point of the resin composition is determined as follows. First, a differential scanning calorimeter is used to completely melt the resin composition after heating. As a differential scanning calorimeter, for example, a differential scanning calorimeter "DSC7000X" manufactured by Hitachi High-Technologies Corporation is used. Next, the obtained molten material is cooled and heated again. Then, the temperature corresponding to the endothermic peak observed during the heating process is determined as the melting point of the resin composition. It should be noted that, in the case where the endothermic peak is not easy to observe by the above-mentioned method, the melting point of the resin composition is determined by texture observation under the orthogonal Nicol conditions of a polarizing microscope. It should be noted that when the melting point of the resin composition is determined according to the state of the resin sheet or laminated substrate described later, in the above-mentioned method, the object of measurement is changed from the resin composition to the resin sheet.
[0100] The melt tension of the resin composition at a temperature 20°C higher than the melting point of the resin composition is measured using a melt tension measuring device at a temperature 20°C higher than the melting point of the resin composition determined by the above method. As a melt tension measuring device, for example, Capilograph (registered trademark) "F-1" manufactured by Toyo Seiki Seisaku-sho Co., Ltd. is used. It should be noted that when the melt tension of the resin composition at a temperature 20°C higher than the melting point of the resin composition is determined according to the state of the resin sheet or laminated substrate described later, in the above method, the measurement object can be changed from the resin composition to the resin sheet.
[0101] The melting point of the resin composition of the present invention is preferably 275°C or higher and 330°C or lower.
[0102] When the melting point of the resin composition of the present invention is lower than 275° C., when a laminated substrate having a resin sheet including the resin composition of the present invention is incorporated into an electronic device by reflow soldering, the heat resistance of the resin sheet may be insufficient.
[0103] When the melting point of the resin composition of the present invention is higher than 330° C., a higher processing temperature is required when molding the resin composition of the present invention into a sheet shape, and thus degradation of the liquid crystal polymer contained in the resin composition of the present invention may be accelerated.
[0104] The resin sheet of the present invention is characterized by comprising the resin composition of the present invention.
[0105] In this specification, a sheet and a film are synonymous, and the two are not distinguished by thickness.
[0106] Figure 1 This is a schematic cross-sectional view showing an example of the resin sheet of the present invention.
[0107] Figure 1 The resin sheet 1 shown has a first main surface 1 a and a second main surface 1 b which are opposed to each other in the thickness direction.
[0108] The thickness of the resin sheet 1 is preferably 10 μm or more and 250 μm or less.
[0109] The resin sheet 1 includes a resin composition 1s containing a liquid crystal polymer 1g and an inorganic filler 1h.
[0110] The resin composition 1s corresponds to the resin composition of the present invention.
[0111] The characteristics of the liquid crystal polymer 1g are the same as those of the liquid crystal polymer contained in the resin composition of the present invention described above.
[0112] The characteristics of the inorganic filler 1h are the same as those of the inorganic filler contained in the resin composition of the present invention. That is, in the resin sheet 1, the specific surface area of the inorganic filler 1h is 30 m 2 / cm 3 The following essential features of the inorganic filler 1h are that the maximum diameter of the inorganic filler 1h is 100 μm or less and the content of the inorganic filler 1h is 0.1 vol % or more and 60 vol % or less.
[0113] like Figure 1 In this case, even if the resin sheet 1 contains the inorganic filler 1h, the orientation of the liquid crystal polymer 1g is unlikely to decrease, and therefore, the tensile elongation at break of the resin sheet 1 is unlikely to decrease.
[0114] like Figure 1 As shown, when the inorganic filler 1h is plate-shaped, the inorganic filler 1h is preferably oriented in the in-plane direction of the resin sheet 1. In this case, the linear expansion coefficient in the in-plane direction of the resin sheet 1 is likely to be small, so when the resin sheet with a conductor layer or a laminated substrate described later is formed using the resin sheet 1, the linear expansion coefficient in the in-plane direction of the resin sheet 1 can be made close to the linear expansion coefficient in the in-plane direction of the conductor layer (for example, copper foil). As a result, in the resin sheet with a conductor layer or the laminated substrate, warping due to the difference in the linear expansion coefficient in the in-plane direction between the resin sheet 1 and the conductor layer is less likely to occur.
[0115] The state where the inorganic filler is oriented in the in-plane direction of the resin sheet means that the orientation direction of the inorganic filler is substantially parallel to the in-plane direction of the resin sheet when the entire resin sheet is observed, but the orientation direction of the inorganic filler does not need to be strictly parallel to the in-plane direction of the resin sheet.
[0116] like Figure 1 As shown, the inorganic filler 1 h preferably does not aggregate. In this case, the physical properties of the resin sheet 1 derived from the inorganic filler 1 h are unlikely to vary depending on the position in the resin sheet 1 .
[0117] like Figure 1 As shown, the inorganic filler 1h is preferably less in the vicinity of the first main surface 1a of the resin sheet 1, and more preferably does not exist in the vicinity of the first main surface 1a of the resin sheet 1. In this case, in the resin sheet with a conductor layer or a laminated substrate described later, even if the conductor layer (for example, copper foil) is adjacent to the first main surface 1a side of the resin sheet 1, the decrease in the adhesion between the resin sheet 1 and the conductor layer due to the inorganic filler 1h is suppressed.
[0118] like Figure 1 As shown, the inorganic filler 1h is preferably less in the vicinity of the second main surface 1b of the resin sheet 1 in addition to the vicinity of the first main surface 1a of the resin sheet 1, and more preferably does not exist in the vicinity of the second main surface 1b of the resin sheet 1.
[0119] That is, the inorganic filler 1h is preferably less in the vicinity of at least one of the first main surface 1a and the second main surface 1b of the resin sheet 1, and more preferably does not exist in the vicinity of at least one of the first main surface 1a and the second main surface 1b of the resin sheet 1.
[0120] In this specification, when the position separated from the first main surface by 1 / 5 of the thickness of the resin sheet in the thickness direction and the position separated from the first main surface by 5 μm in the thickness direction, whichever is shorter, is defined as the first vicinity, the vicinity of the first main surface of the resin sheet refers to the region between the first main surface and the first vicinity. When the position separated from the second main surface by 1 / 5 of the thickness of the resin sheet in the thickness direction and the position separated from the second main surface by 5 μm in the thickness direction, whichever is shorter, is defined as the second vicinity, the vicinity of the second main surface of the resin sheet refers to the region between the second main surface and the second vicinity.
[0121] Figure 2 is an example of the resin sheet of the present invention, and is a diagram showing Figure 1 Schematic cross-sectional views of different examples.
[0122] Figure 2The resin sheet 1 ′ shown includes a resin composition 1 s ′, and the resin composition 1 s ′ includes a liquid crystal polymer 1 g and an inorganic filler 1 h.
[0123] In the resin sheet 1 ′, the inorganic filler 1 h is subjected to surface treatment. More specifically, in the resin sheet 1 ′, the surface treatment layer 3 is provided on the surface of the inorganic filler 1 h.
[0124] Figure 3 is an example of the resin sheet of the present invention, and is a diagram showing Figure 1 and Figure 2 Schematic cross-sectional views of different examples.
[0125] Figure 3 The resin sheet 1 ″ shown includes a resin composition 1 s ″, and the resin composition 1 s ″ includes a liquid crystal polymer 1 g and an inorganic filler 1 h ″.
[0126] In the resin sheet 1 ″, the inorganic filler 1 h ″ is spherical.
[0127] The method for producing a resin sheet of the present invention is characterized by comprising the steps of: preparing a resin composition comprising a liquid crystal polymer and a 2 / cm 3 An inorganic filler having a maximum diameter of 100 μm or less and a maximum diameter of 100 μm or less, wherein the content of the inorganic filler is 0.1 vol % or more and 60 vol % or less; and forming the resin composition into a sheet by melt extrusion.
[0128] <Step of Preparing Resin Composition>
[0129] A resin composition is prepared, the resin composition comprising a liquid crystal polymer and a specific surface area of 30 m 2 / cm 3 The inorganic filler has a maximum diameter of 100 μm or less, and the content of the inorganic filler is 0.1 vol% or more and 60 vol% or less, that is, the resin composition of the present invention is prepared. At this time, for example, the liquid crystal polymer and the inorganic filler can be melt-kneaded by a twin-screw extruder to prepare a molten resin composition.
[0130] <Step of forming the resin composition into a sheet>
[0131] The resin composition is formed into a sheet by melt extrusion. In this case, for example, the resin composition in a molten state may be discharged from a T-die and then cooled to form the resin composition into a sheet.
[0132] Based on the above, the resin sheet of the present invention is produced.
[0133] The method for producing a resin sheet of the present invention does not require a step of kneading a molten liquid crystal polymer and an inorganic filler and then pulverizing the mixture as in the method described in Patent Document 3, and thus the resin composition can be formed into a sheet by melt extrusion without causing contamination.
[0134] The resin composition used in the above-mentioned production method is a resin composition comprising a liquid crystal polymer and a specific surface area of 30 m 2 / cm 3 The resin composition of the present invention comprises an inorganic filler having a maximum diameter of 100 μm or less and a content of 0.1 vol % to 60 vol %. Therefore, according to the above-mentioned production method, a resin sheet formed into a sheet by melt extrusion can be produced.
[0135] The resin sheet with a conductor layer of the present invention is characterized by comprising the resin sheet of the present invention and a conductor layer adjacent to at least one main surface side of the resin sheet.
[0136] Figure 4 This is a schematic cross-sectional view showing an example of the resin sheet with a conductor layer of the present invention.
[0137] Figure 4 The resin sheet 10 with a conductor layer shown includes a resin sheet 1 and a conductor layer 2 in the lamination direction.
[0138] In this specification, the lamination direction corresponds to a direction along the thickness direction of the resin sheet constituting the resin sheet with a conductor layer.
[0139] The conductor layer 2 is adjacent to at least one principal surface side of the resin sheet 1 , and is adjacent to the first principal surface 1 a side in this case.
[0140] The conductor layer 2 may be in a planar shape extending along one surface, or may be in a patterned shape such as wiring.
[0141] Examples of the constituent material of the conductor layer 2 include copper, silver, aluminum, stainless steel, nickel, gold, and alloys containing at least one of these metals.
[0142] The conductor layer 2 is made of, for example, a metal foil, and preferably a copper foil among the metal foils. In this case, a metal other than copper may exist on the surface of the copper foil.
[0143] The thickness of the conductor layer 2 is preferably 1 μm or more and 35 μm or less, and more preferably 6 μm or more and 18 μm or less.
[0144] The resin sheet 10 with a conductor layer may further include another conductor layer adjacent to the second main surface 1 b side of the resin sheet 1 in addition to the conductor layer 2 .
[0145] The resin sheet 10 with a conductor layer is produced, for example, by crimping the conductor layer 2 onto the first main surface 1a of the resin sheet 1. The conductor layer 2 may be etched into a pattern shape after being crimped onto the first main surface 1a of the resin sheet 1.
[0146] The resin sheet 10 with a conductor layer can also be produced by pressure-bonding the conductor layer 2 patterned in advance to the first main surface 1 a of the resin sheet 1 .
[0147] The laminated substrate of the present invention is characterized by comprising the resin sheet with a conductor layer of the present invention.
[0148] Figure 5 It is a schematic cross-sectional view showing an example of the laminated substrate of the present invention.
[0149] Figure 5 The laminated substrate 50 shown has a resin sheet 10A with a conductor layer, a resin sheet 10B with a conductor layer, and a resin sheet 10C with a conductor layer in order in the lamination direction. That is, in the laminated substrate 50, the resin sheet 10A with a conductor layer, the resin sheet 10B with a conductor layer, and the resin sheet 10C with a conductor layer are stacked in order in the lamination direction.
[0150] The resin sheet with a conductor layer 10A includes a resin sheet 1A and a conductor layer 2A.
[0151] The resin sheet 1A has a first main surface 1Aa and a second main surface 1Ab that are opposed to each other in the thickness direction.
[0152] The resin sheet 1A includes a resin composition 1As containing a liquid crystal polymer 1Ag and an inorganic filler 1Ah.
[0153] The conductor layer 2A is adjacent to the first principal surface 1Aa side of the resin sheet 1A. Moreover, the conductor layer 2A is also adjacent to the second principal surface 1Bb side of the resin sheet 1B described later.
[0154] The resin sheet with a conductor layer 10B includes a resin sheet 1B, a conductor layer 2B, a conductor layer 2B′, and a conductor layer 2B″.
[0155] The resin sheet 1B has a first main surface 1Ba and a second main surface 1Bb that are opposed to each other in the thickness direction.
[0156] The resin sheet 1B includes a resin composition 1Bs including a liquid crystal polymer 1Bg and an inorganic filler 1Bh.
[0157] The conductor layers 2B, 2B' and 2B" are adjacent to the first principal surface 1Ba side of the resin sheet 1B. The conductor layers 2B, 2B' and 2B" are also adjacent to the second principal surface 1Cb side of the resin sheet 1C described later.
[0158] The resin sheet with a conductor layer 10C includes a resin sheet 1C and a conductor layer 2C.
[0159] The resin sheet 1C has a first main surface 1Ca and a second main surface 1Cb that are opposed to each other in the thickness direction.
[0160] The resin sheet 1C includes a resin composition 1Cs including a liquid crystal polymer 1Cg and an inorganic filler 1Ch.
[0161] The conductive layer 2C is adjacent to the first main surface 1Ca side of the resin sheet 1C.
[0162] like Figure 5 As shown, the conductor layer 2B is preferably provided across the interface between the resin sheet 1B and the resin sheet 1C. As a result, the interface between the conductor layer 2B and the resin sheet 1B and the interface between the conductor layer 2B and the resin sheet 1C are offset from the interface between the resin sheet 1B and the resin sheet 1C in the stacking direction, thereby suppressing peeling at the interface between the conductor layer 2B and the resin sheet 1B and the interface between the conductor layer 2B and the resin sheet 1C.
[0163] The conductor layer 2B′ and the conductor layer 2B″ are also preferably provided across the interface between the resin sheet 1B and the resin sheet 1C, similarly to the conductor layer 2B.
[0164] It should be noted that in Figure 5 In the figure, the interface between the resin sheet 1B and the resin sheet 1C is shown, but in fact, the interface may not be clearly shown. Figure 5 In the cross section along the stacking direction shown, a plane passing through the center of the cross section of the conductor layer 2B in the stacking direction and along the in-plane direction perpendicular to the stacking direction is regarded as the interface between the resin sheet 1B and the resin sheet 1C.
[0165] In at least one of the resin sheet 1A (resin composition 1As), the resin sheet 1B (resin composition 1Bs), and the resin sheet 1C (resin composition 1Cs), the specific surface area of the inorganic filler is 30 m 2 / cm 3 The maximum diameter of the inorganic filler is 100 μm or less, and the content of the inorganic filler is 0.1 vol % or more and 60 vol % or less.
[0166] That is, the laminated substrate 50 only needs to have at least one inorganic filler having a specific surface area of 30 m 2 / cm 3 The resin sheet may have a specific surface area of 30 m2 or less, a maximum diameter of the inorganic filler of 100 μm or less, and a content of the inorganic filler of 0.1 vol% or more and 60 vol% or less.2 / cm 3 The present invention relates to a resin sheet in which the maximum diameter of the inorganic filler is 100 μm or less and the content of the inorganic filler is 0.1 vol % or more and 60 vol % or less.
[0167] It is preferable that all of the resin sheets 1A, 1B, and 1C satisfy the specific surface area of the inorganic filler of 30 m 2 / cm 3 The maximum diameter of the inorganic filler is 100 μm or less, and the content of the inorganic filler is 0.1 vol % or more and 60 vol % or less.
[0168] The thicknesses of the resin sheets 1A, 1B, and 1C may be the same as or different from each other, or may be different from each other. Figure 5 Some parts are different as shown.
[0169] As the constituent materials of the conductor layer 2A, the conductor layer 2B, the conductor layer 2B', the conductor layer 2B", and the conductor layer 2C, similar to the constituent materials of the conductor layer 2, for example, copper, silver, aluminum, stainless steel, nickel, gold, and alloys containing at least one of these metals are given.
[0170] Conductive layer 2A, conductive layer 2B, conductive layer 2B', conductive layer 2B" and conductive layer 2C are made of metal foil, for example, similarly to conductive layer 2, and preferably copper foil. In this case, metal other than copper may exist on the surface of the copper foil.
[0171] The constituent materials of the conductor layer 2A, the conductor layer 2B, the conductor layer 2B′, the conductor layer 2B″, and the conductor layer 2C are preferably the same as each other, but may be different from each other or may be partially different.
[0172] The thickness of the conductor layer 2A, the conductor layer 2B, the conductor layer 2B′, the conductor layer 2B″ and the conductor layer 2C can be as follows: Figure 5 They may be the same as shown, or they may be different from each other, or they may be partially different.
[0173] The laminated substrate 50 has three resin sheets with conductor layers in the lamination direction, but may have only one, two, or four or more.
[0174] The laminated substrate 50 is as follows Figure 5 As shown in the figure, it is preferable to further include an interlayer connection conductor which is provided so as to penetrate the resin sheet in the stacking direction but not penetrate the conductor layer in the stacking direction and is connected to the conductor layer.
[0175] Figure 5The illustrated multilayer substrate 50 further includes an interlayer connection conductor 20A, an interlayer connection conductor 20B, an interlayer connection conductor 20C, and an interlayer connection conductor 20D.
[0176] The interlayer connection conductor 20A is provided so as to penetrate the resin sheet 1B in the stacking direction, but does not penetrate the conductor layer 2B' in the stacking direction, and is connected to the conductor layer 2B'. More specifically, the interlayer connection conductor 20A penetrates the resin sheet 1B in the stacking direction, and is connected to the conductor layer 2B' on the first main surface 1Ba side of the resin sheet 1B. In addition, the interlayer connection conductor 20A is connected to the conductor layer 2A on the second main surface 1Bb side of the resin sheet 1B. That is, the conductor layer 2A and the conductor layer 2B' are electrically connected via the interlayer connection conductor 20A.
[0177] The interlayer connection conductor 20B is provided at a position separated from the interlayer connection conductor 20A so as to penetrate the resin sheet 1B in the stacking direction but not penetrate the conductor layer 2B″ in the stacking direction and is connected to the conductor layer 2B″. More specifically, the interlayer connection conductor 20B penetrates the resin sheet 1B in the stacking direction at a position separated from the interlayer connection conductor 20A and is connected to the conductor layer 2B″ on the first main surface 1Ba side of the resin sheet 1B. In addition, the interlayer connection conductor 20B is connected to the conductor layer 2A on the second main surface 1Bb side of the resin sheet 1B at a position separated from the interlayer connection conductor 20A. That is, the conductor layer 2A and the conductor layer 2B″ are electrically connected via the interlayer connection conductor 20B.
[0178] The interlayer connection conductor 20C is provided so as to penetrate the resin sheet 1C in the stacking direction, but does not penetrate the conductor layer 2C in the stacking direction, and is connected to the conductor layer 2C. More specifically, the interlayer connection conductor 20C penetrates the resin sheet 1C in the stacking direction, and is connected to the conductor layer 2C on the first main surface 1Ca side of the resin sheet 1C. In addition, the interlayer connection conductor 20C is connected to the conductor layer 2B' on the second main surface 1Cb side of the resin sheet 1C. That is, the conductor layer 2B' and the conductor layer 2C are electrically connected via the interlayer connection conductor 20C.
[0179] The interlayer connection conductor 20D is provided at a position separated from the interlayer connection conductor 20C so as to penetrate the resin sheet 1C in the stacking direction but not penetrate the conductor layer 2C in the stacking direction, and is connected to the conductor layer 2C. More specifically, the interlayer connection conductor 20D penetrates the resin sheet 1C in the stacking direction at a position separated from the interlayer connection conductor 20C and is connected to the conductor layer 2C on the first main surface 1Ca side of the resin sheet 1C. In addition, the interlayer connection conductor 20D is connected to the conductor layer 2B″ on the second main surface 1Cb side of the resin sheet 1C at a position separated from the interlayer connection conductor 20C. That is, the conductor layer 2B″ and the conductor layer 2C are electrically connected via the interlayer connection conductor 20D.
[0180] Thus, in the laminated substrate 50, the conductor layer 2A and the conductor layer 2C are electrically connected via the interlayer connection conductor 20A, the conductor layer 2B', and the interlayer connection conductor 20C. In addition, in the laminated substrate 50, the conductor layer 2A and the conductor layer 2C are also electrically connected via the interlayer connection conductor 20B, the conductor layer 2B'', and the interlayer connection conductor 20D.
[0181] The interlayer connection conductor 20A is formed, for example, by plating the inner wall of a via hole that penetrates the resin sheet 1B in the thickness direction but does not penetrate the conductor layer 2B' in the thickness direction and reaches the conductor layer 2B', or by heat treating the via hole after filling the via hole with a conductive paste.
[0182] The interlayer connection conductor 20B, the interlayer connection conductor 20C, and the interlayer connection conductor 20D are formed in the same manner as the interlayer connection conductor 20A except that the formation positions are different.
[0183] When the interlayer connection conductors 20A, 20B, 20C, and 20D are formed by plating, examples of metals constituting each of the interlayer connection conductors include copper, tin, and silver, and copper is preferred.
[0184] When the interlayer connection conductor 20A, the interlayer connection conductor 20B, the interlayer connection conductor 20C, and the interlayer connection conductor 20D are formed by heat treatment of the conductive paste, examples of the metal contained in each interlayer connection conductor include copper, tin, silver, etc. Among them, each interlayer connection conductor preferably contains copper, and more preferably contains copper and tin. For example, when the interlayer connection conductor 20A contains copper and tin and the conductor layer 2B' includes copper foil, the interlayer connection conductor 20A reacts with the conductor layer 2B' at low temperature to form an alloy, so that the two are easily conductive. The same is true for other combinations of interlayer connection conductors and conductor layers.
[0185] When the interlayer connecting conductors 20A, 20B, 20C and 20D are formed by heat treatment of a conductive paste, the resin contained in each interlayer connecting conductor preferably includes at least one thermosetting resin selected from the group consisting of epoxy resins, phenolic resins, polyimide resins, silicone resins or modified resins thereof, and acrylic resins, or at least one thermoplastic resin selected from the group consisting of polyamide resins, polystyrene resins, polymethacrylic resins, polycarbonate resins and cellulose resins.
[0186] The multilayer substrate 50 is used as, for example, an electronic circuit substrate.
[0187] In the laminated substrate 50, the conductor layer 2B may be a signal line for transmitting a signal. That is, the laminated substrate 50 may include the conductor layer 2B as a signal line for transmitting a signal. In this case, the laminated substrate 50 constitutes a transmission line.
[0188] The multilayer substrate 50 may include the conductor layer 2B as a signal line for transmitting a signal, and the conductor layer 2A and the conductor layer 2C as ground electrodes. In this case, the multilayer substrate 50 forms a stripline transmission line.
[0189] When the multilayer substrate 50 forms the above-mentioned transmission line, the conductor layer 2B may be a signal line that transmits a high-frequency signal.
[0190] When the laminated substrate 50 constitutes a transmission line, the resin sheet 1B including the liquid crystal polymer 1Bg with a low dielectric constant and the resin sheet 1C including the liquid crystal polymer 1Cg with a low dielectric constant are connected to the conductor layer 2B, that is, the signal line. Therefore, the transmission characteristics of the laminated substrate 50 are easily improved.
[0191] The multilayer substrate 50 is produced, for example, by the following method.
[0192] <Step of producing a resin sheet with a conductor layer>
[0193] Figure 6 , Figure 7 and Figure 8 This is a schematic cross-sectional view showing a step of preparing a resin sheet with a conductor layer in one example of the method for producing a laminated substrate of the present invention.
[0194] like Figure 6 As shown, a resin sheet 10A with a conductor layer is produced in which the conductor layer 2A is provided adjacent to the first main surface 1Aa side of the resin sheet 1A. At this time, for example, the conductor layer 2A is pressure-bonded to the first main surface 1Aa of the resin sheet 1A.
[0195] like Figure 7 As shown, a resin sheet 10B with a conductor layer is prepared in which the conductor layer 2B, the conductor layer 2B' and the conductor layer 2B" are provided adjacent to the first main surface 1Ba side of the resin sheet 1B. At this time, for example, after the conductor layer is crimped to the first main surface 1Ba of the resin sheet 1B, the conductor layer 2B, the conductor layer 2B' and the conductor layer 2B" are patterned by etching the conductor layer. Alternatively, the conductor layer 2B, the conductor layer 2B' and the conductor layer 2B" are prepared in advance, and each conductor layer is crimped to the first main surface 1Ba of the resin sheet 1B.
[0196] like Figure 8 As shown, a resin sheet 10C with a conductor layer is produced in which the conductor layer 2C is provided adjacent to the first main surface 1Ca side of the resin sheet 1C. At this time, for example, the conductor layer 2C is pressure-bonded to the first main surface 1Ca of the resin sheet 1C.
[0197] <Via hole forming process>
[0198] Fig. 9 and Fig.10 This is a schematic cross-sectional view showing a step of forming a via hole in one example of the method for manufacturing a laminated substrate of the present invention.
[0199] like Fig. 9 As shown, in the resin sheet 10B with a conductor layer, the via hole 21A is formed to penetrate the resin sheet 10B in the thickness direction but not to penetrate the conductor layer 2B' in the thickness direction to reach the conductor layer 2B'. Thus, a part of the conductor layer 2B' is exposed from the via hole 21A.
[0200] In addition, in the resin sheet 10B with a conductor layer, a via hole 21B is formed at a position separated from the position where the via hole 21A is to be formed so as to penetrate the resin sheet 10B in the thickness direction but not penetrate the conductor layer 2B″ in the thickness direction to reach the conductor layer 2B″. As a result, a portion of the conductor layer 2B″ is exposed from the via hole 21B.
[0201] In the above, the via hole 21A and the via hole 21B are formed in the resin sheet 10B with a conductor layer. At this time, the via hole 21A and the via hole 21B may be formed at the same timing or at different timings.
[0202] like Fig.10 As shown, in the resin sheet 10C with a conductor layer, a via hole 21C is formed so as to penetrate the resin sheet 10C in the thickness direction but not penetrate the conductor layer 2C in the thickness direction to reach the conductor layer 2C. Thus, a part of the conductor layer 2C is exposed from the via hole 21C.
[0203] In addition, in the resin sheet 10C with a conductor layer, a via hole 21D is formed at a position separated from the position where the via hole 21C is to be formed, so as to penetrate the resin sheet 10C in the thickness direction but not penetrate the conductor layer 2C in the thickness direction to reach the conductor layer 2C. As a result, a part of the conductor layer 2C is exposed from the via hole 21D.
[0204] In the above, the via hole 21C and the via hole 21D are formed in the resin sheet with a conductor layer 10C. At this time, the via hole 21C and the via hole 21D may be formed at the same timing or at different timings.
[0205] When forming the via hole 21A, the via hole 21B, the via hole 21C, and the via hole 21D, it is preferable to irradiate the resin sheet with a conductor layer with a laser from the resin sheet side.
[0206] <Conductive paste filling process>
[0207] Fig.11 and Fig.12 This is a schematic cross-sectional view showing a step of filling a conductive paste in one example of the method for producing a laminated substrate of the present invention.
[0208] like Fig.11 As shown, conductive paste 22A is filled into via 21A of resin sheet 10B with a conductor layer. Also, conductive paste 22B is filled into via 21B of resin sheet 10B with a conductor layer. At this time, conductive paste 22A and conductive paste 22B may be filled at the same time or at different times.
[0209] like Fig.12 As shown, for the resin sheet 10C with a conductor layer, the conductive paste 22C is filled into the via hole 21C. Also, for the resin sheet 10C with a conductor layer, the conductive paste 22D is filled into the via hole 21D. At this time, the conductive paste 22C and the conductive paste 22D may be filled at the same time, or may be filled at different times.
[0210] Examples of a method for filling conductive paste 22A, conductive paste 22B, conductive paste 22C, and conductive paste 22D include a screen printing method and a vacuum filling method.
[0211] Conductive paste 22A, conductive paste 22B, conductive paste 22C, and conductive paste 22D each contain, for example, metal and resin.
[0212] Examples of the metal contained in each of conductive paste 22A, conductive paste 22B, conductive paste 22C, and conductive paste 22D include copper, tin, silver, etc. Among them, each conductive paste preferably contains copper, and more preferably contains copper and tin.
[0213] The resin contained in each conductive paste of conductive paste 22A, conductive paste 22B, conductive paste 22C and conductive paste 22D preferably contains at least one thermosetting resin selected from the group consisting of epoxy resin, phenolic resin, polyimide resin, silicone resin or its modified resin, and acrylic resin, or at least one thermoplastic resin selected from the group consisting of polyamide resin, polystyrene resin, polymethacrylic resin, polycarbonate resin and cellulose resin.
[0214] Each of conductive paste 22A, conductive paste 22B, conductive paste 22C, and conductive paste 22D may further contain a carrier, a solvent, a thixotropic agent, an activator, and the like.
[0215] Examples of the carrier include rosin-based resins including rosin and its modified derivatives such as modified rosin, synthetic resins including rosin and its modified derivatives such as modified rosin, and mixtures of these resins.
[0216] Examples of rosin-based resins including rosin and its modified derivatives such as modified rosin include gum rosin, tall rosin, wood rosin, polymerized rosin, hydrogenated rosin, formylated rosin, rosin resin, rosin-modified maleic acid resin, rosin-modified phenolic resin, rosin-modified alkyd resin, and other various rosin derivatives.
[0217] Examples of the synthetic resin including rosin and its modified derivatives such as modified rosin include polyester resins, polyamide resins, phenoxy resins, and terpene resins.
[0218] As the solvent, for example, alcohol, ketone, lipid, ether, aromatic series, hydrocarbon, etc. are mentioned. As specific examples thereof, benzyl alcohol, ethanol, isopropanol, butanol, diethylene glycol, ethylene glycol, glycerol, ethyl cellosolve, butyl cellosolve, ethyl acetate, butyl acetate, butyl benzoate, diethyl adipate, dodecane, tetradecene, α-terpineol, terpineol, 2-methyl-2,4-pentanediol, 2-ethylhexanediol, toluene, xylene, propylene glycol monophenyl ether, diethylene glycol monohexyl ether, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, diethylene glycol monoethyl ether, diisobutyl adipate, hexanediol, cyclohexanedimethanol, 2-terpineoxyethanol, 2-dihydroterpineoxyethanol, and mixtures thereof are mentioned. Among them, terpineol, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, or diethylene glycol monoethyl ether is preferred.
[0219] Examples of the thixotropic agent include hydrogenated castor oil, carnauba wax, amides, hydroxy fatty acids, dibenzylidene sorbitol, bis(p-methylbenzylidene)sorbitol, beeswax, stearic acid amide, hydroxystearic acid ethylenebisamide, etc. In addition, fatty acids such as caprylic acid, lauric acid, myristic acid, palmitic acid, stearic acid, and behenic acid, hydroxy fatty acids such as 1,2-hydroxystearic acid, antioxidants, surfactants, amines, etc. may be added to these thixotropic agents as needed.
[0220] Examples of the activator include amine hydrohalides, organic halogen compounds, organic acids, organic amines, and polyols.
[0221] Examples of the amine hydrohalide salt include diphenylguanidine hydrobromide, diphenylguanidine hydrochloride, cyclohexylamine hydrobromide, ethylamine hydrochloride, ethylamine hydrobromide, diethylaniline hydrobromide, diethylaniline hydrobromide, triethanolamine hydrobromide, and monoethanolamine hydrobromide.
[0222] Examples of the organic halogen compound include chlorinated paraffin, tetrabromoethane, dibromopropanol, 2,3-dibromo-1,4-butanediol, 2,3-dibromo-2-butene-1,4-diol, and tris(2,3-dibromopropyl)isocyanurate.
[0223] Examples of the organic acid include malonic acid, fumaric acid, glycolic acid, citric acid, malic acid, succinic acid, phenylsuccinic acid, maleic acid, salicylic acid, anthranilic acid, glutaric acid, suberic acid, adipic acid, sebacic acid, stearic acid, abietic acid, benzoic acid, trimellitic acid, pyromellitic acid, and dodecanoic acid.
[0224] Examples of the organic amine include monoethanolamine, diethanolamine, triethanolamine, tributylamine, aniline, and diethylaniline.
[0225] Examples of the polyol include erythritol, pyrogallol, and ribitol.
[0226] <Step of forming an interlayer connection conductor>
[0227] Fig.13 This is a schematic cross-sectional view showing a step of forming an interlayer connection conductor in one example of the method for manufacturing a laminated substrate according to the present invention.
[0228] like Fig.13 As shown, a resin sheet 10A with a conductor layer, a resin sheet 10B with a conductor layer filled with conductive paste 22A and conductive paste 22B, and a resin sheet 10C with a conductor layer filled with conductive paste 22C and conductive paste 22D are stacked in sequence in the stacking direction. At this time, the stacking is such that the surface (upper surface) on the conductor layer 2A side of the resin sheet 10A with a conductor layer is in contact with the surface (lower surface) on the resin sheet 1B side of the resin sheet 10B with a conductor layer, and the surface (upper surface) on the conductor layer 2B side (conductor layer 2B' side, conductor layer 2B'' side) of the resin sheet 10B with a conductor layer is in contact with the surface (lower surface) on the resin sheet 1C side of the resin sheet 10C with a conductor layer. It should be noted that in Fig.13 In the figure, for convenience of explanation, the resin sheets with conductor layers are shown separated from each other.
[0229] Then, the obtained laminate is heated and pressure is applied in the lamination direction, thereby performing hot pressing. As a result, the resin sheet 10A with a conductor layer is pressed against the resin sheet 10B with a conductor layer, and the resin sheet 10B with a conductor layer is pressed against the resin sheet 10C with a conductor layer. In addition, the conductive paste 22A, the conductive paste 22B, the conductive paste 22C, and the conductive paste 22D are cured during the hot pressing process to form the interlayer connection conductor 20A, the interlayer connection conductor 20B, the interlayer connection conductor 20C, and the interlayer connection conductor 20D, respectively. In this way, the interlayer connection conductor 20A, the interlayer connection conductor 20B, the interlayer connection conductor 20C, and the interlayer connection conductor 20D are formed in the via 21A, the via 21B, the via 21C, and the via 21D, respectively.
[0230] When forming the interlayer connection conductors 20A, 20B, 20C, and 20D, instead of filling the via holes with a conductive paste, the inner walls of the via holes may be plated with a metal such as copper, tin, or silver.
[0231] In the above, when forming an interlayer connecting conductor, an example is given of filling a via with a conductive paste or performing a plating treatment on a via that passes through a resin sheet in the thickness direction but does not pass through the conductor layer in the thickness direction but reaches the conductor layer. However, an interlayer connecting conductor can also be formed by filling a via with a conductive paste or performing a plating treatment on a via that passes through both the resin sheet and the conductor layer in the thickness direction.
[0232] Through the above, we can produce Figure 5 The laminated substrate 50 is shown.
[0233] Example
[0234] Hereinafter, examples which more specifically disclose the resin composition of the present invention and the resin sheet of the present invention will be shown. It should be noted that the present invention is not limited to the following examples.
[0235] [Examples 1 to 8]
[0236] The resin compositions and resin sheets of Examples 1 to 8 were produced by the following method.
[0237] First, the liquid crystal polymer and the inorganic filler shown in Table 1 were melt-kneaded by a twin-screw extruder to produce a molten resin composition. Table 1 shows the contents of the liquid crystal polymer and the inorganic filler in the resin composition.
[0238] Then, the molten resin composition is discharged from the T-die and then cooled, thereby forming the resin composition into a sheet shape.
[0239] [Comparative Examples 1 to 6]
[0240] Resin compositions and resin sheets of Comparative Examples 1 to 6 were produced in the same manner as in Examples 1 to 8 except that the liquid crystal polymers and inorganic fillers shown in Table 2 were used.
[0241] [Comparative Example 7]
[0242] After the resin composition of Comparative Example 7 was produced using the liquid crystal polymers shown in Table 2 and the inorganic fillers shown in Table 2, a resin sheet of Comparative Example 7 was produced according to Production Example 1 described in Patent Document 3.
[0243] It should be noted that the liquid crystal polymers A and B shown in Tables 1 and 2 are as follows.
[0244] Liquid crystal polymer A: copolymer of 73 mol% p-hydroxybenzoic acid and 27 mol% 6-hydroxy-2-naphthoic acid
[0245] Liquid crystal polymer B: copolymer of 80 mol% p-hydroxybenzoic acid and 20 mol% 6-hydroxy-2-naphthoic acid
[0246] In addition, the properties of the inorganic fillers shown in Tables 1 and 2 were determined as follows.
[0247] <Specific surface area>
[0248] First, the inorganic filler was degassed at 150°C for 20 minutes. Then, the specific surface area of the inorganic filler was measured by the BET 1-point method using a fully automatic specific surface area measuring device "Macsorb (registered trademark)" manufactured by Mountech. Specifically, the specific surface area of the inorganic filler was calculated based on the amount of nitrogen adsorbed on the surface of the inorganic filler weighed to a degree of 0.1 g or more and 1.0 g or less.
[0249] <Maximum diameter>
[0250] First, the inorganic filler is ultrasonically dispersed in ethanol. Afterwards, the particle size distribution of the inorganic filler is measured by laser diffraction / scattering method using a laser diffraction / scattering particle size distribution measuring device "LA-960" manufactured by Horiba, Ltd. At this time, the particle size of the inorganic filler is measured as the equivalent circle diameter. Then, the maximum particle size in the obtained particle size distribution of the inorganic filler is determined as the maximum diameter of the inorganic filler.
[0251] <Average particle size>
[0252] First, the volume-based cumulative particle size distribution of the inorganic filler is obtained by converting the particle size distribution of the inorganic filler obtained when determining the maximum diameter of the inorganic filler into a particle size distribution represented by cumulative probability. Then, the median particle size D is obtained based on the obtained volume-based cumulative particle size distribution of the inorganic filler.50 , the median particle size D 50 Determined as the average particle size of the inorganic filler.
[0253] <Thickness>
[0254] First, an image of the inorganic filler is taken by a scanning electron microscope. Next, the image of the inorganic filler obtained is analyzed by analysis software, thereby measuring the size of the inorganic filler in the short side direction. Then, 100 inorganic fillers are measured for the size in the short side direction, and the average value of the 100 measured values obtained is determined as the thickness of the inorganic filler.
[0255] <Aspect Ratio>
[0256] First, an image of an inorganic filler was taken by a scanning electron microscope. Next, the image of the inorganic filler obtained was subjected to image analysis by analysis software, thereby measuring the size in the short side direction of the inorganic filler and the size in the long side direction of the inorganic filler. Then, 100 inorganic fillers were subjected to the above-mentioned size measurement in the short side direction and the long side direction, and the average value of 100 measured values obtained as the size in the short side direction was set to A, and the average value of 100 measured values obtained as the size in the long side direction was set to B, and B / A at this time was determined as the aspect ratio of the inorganic filler.
[0257] In addition, when the inorganic filler is spherical, the thickness and aspect ratio of the inorganic filler are not determined.
[0258] [evaluate]
[0259] The following evaluations were performed on Examples 1 to 8 and Comparative Examples 1 to 7. Tables 1 and 2 show the results.
[0260] <Melting point>
[0261] Using a differential scanning calorimeter "DSC7000X" manufactured by Hitachi High-Technologies Corporation, the resin sheet was heated at a heating rate of 20°C / min and completely melted. Next, the resulting melt was cooled to 175°C at a cooling rate of 20°C / min, and then heated again at a heating rate of 20°C / min. Then, the temperature corresponding to the endothermic peak observed during the heating process was determined as the melting point of the resin composition contained in the resin sheet. It should be noted that when the endothermic peak is not easy to observe by the above method, the melting point of the resin composition contained in the resin sheet is determined by texture observation under the orthogonal Nicol conditions of a polarizing microscope.
[0262] <Melt tension>
[0263] The melt tension of the resin composition contained in the resin sheet was measured using Capilograph (registered trademark) "F-1" manufactured by Toyo Seiki Seisaku-sho, Ltd. at a temperature 20°C higher than the melting point of the resin composition determined by the above method. At this time, the cylinder diameter was set to 9.55 mm, the capillary diameter was set to 1 mm, and the strand drawing speed was set to 150 m / min.
[0264] <Can it be made into sheets>
[0265] Whether the resin composition could be formed into a sheet was evaluated according to the following criteria. In the case where the resin composition could be formed into a sheet, the thickness of the obtained resin sheet was 100 μm.
[0266] The resin composition can be formed into a sheet without breaking during the cooling process of the <step of forming the resin composition into a sheet>.
[0267] Unable to form the resin composition into a sheet: The resin composition was broken during the cooling process of the <step of forming the resin composition into a sheet>, and the resin composition could not be formed into a sheet.
[0268] Pollution
[0269] First, the resin sheet was heated from room temperature to 600°C at a heating rate of 10°C / min in an air atmosphere using a thermogravimetric / differential thermal simultaneous measurement device, and then left at 600°C for 45 minutes to remove the resin component (liquid crystal polymer, etc.) from the resin sheet. Then, the inorganic component remaining after the resin component was removed was subjected to elemental analysis using a transmission electron microscope-energy dispersive X-ray analysis (SEM-EDX), thereby evaluating the presence or absence of contamination in the resin sheet according to the following criteria.
[0270] Yes: As a result of elemental analysis of inorganic components, iron components were detected.
[0271] None: As a result of elemental analysis of inorganic components, no iron component was detected.
[0272] <Water absorption>
[0273] First, five 50mm×50mm samples were cut out from the resin sheet. Next, the five samples were placed in an oven set at 130°C for 30 minutes, and then placed in a dryer and cooled to room temperature. Then, the total weight M1 of the five samples was measured. Next, the five samples were completely immersed in distilled water at room temperature and left for 24 hours, and then the five samples were taken out of the distilled water and the water droplets on the surface of each sample were wiped off. Then, the total weight M2 of the five samples was measured. Then, the calculated value "100×(M2-M1) / M1" (unit: %) was calculated, and this calculated value was set as the water absorption of the resin sheet. The criteria for judging the water absorption are as follows.
[0274] ◎ (Excellent): Water absorption is less than 0.05%.
[0275] ○ (good): The water absorption rate is higher than 0.05% and is 0.10% or less.
[0276] <Tensile elongation at break>
[0277] The tensile test of the resin sheet was carried out in accordance with "ASTM D882", the size of the resin sheet before the tensile test in the tensile direction was set to L1, and the size of the resin sheet when it broke during the tensile test was set to L2, and the calculated value "100×(L2-L1) / L1" (unit: %) was obtained. In this evaluation, for the resin sheet, the flow direction (MD) of the resin sheet corresponding to the direction of discharging the resin composition from the T-die when manufacturing the resin sheet and the vertical direction (TD) orthogonal to the flow direction of the resin sheet were set as the tensile direction, and 5 tensile tests were carried out for each direction to obtain the above-mentioned calculated value. Then, the average value of these calculated values was determined as the tensile elongation at break of the resin sheet. It should be noted that the flow direction and the vertical direction of the resin sheet are directions included in the in-plane direction orthogonal to the thickness direction. The criteria for determining the tensile elongation at break are as follows.
[0278] ◎ (Excellent): The tensile elongation at break is 10% or more.
[0279] ○ (good): The tensile elongation at break is 5% or more and less than 10%.
[0280] × (bad): The tensile elongation at break is less than 5%.
[0281] <Linear expansion coefficient in the in-plane direction>
[0282] First, a 20mm×4mm sample was cut out from the resin sheet and placed on the probe of a thermomechanical analyzer manufactured by Seiko Instruments with a chuck distance of 10mm. Next, a load of 5g was applied to the sample, and the temperature was raised to 170°C at a heating rate of 40°C / min, and then cooled to 30°C at a cooling rate of 10°C / min. Then, during the cooling process, the linear expansion coefficient of the resin sheet was determined by measuring the change in the distance between the chucks in the temperature range of 100°C to 50°C. In this evaluation, the linear expansion coefficients in the flow direction (MD) and the perpendicular direction (TD) of the resin sheet sample were determined by the above method, and their average value was determined as the linear expansion coefficient in the in-plane direction of the resin sheet. The criteria for determining the linear expansion coefficient in the in-plane direction of the resin sheet are as follows.
[0283] ◎ (excellent): The linear expansion coefficient in the in-plane direction is within the range of 16±4 ppm / K.
[0284] ○ (good): The linear expansion coefficient in the in-plane direction is outside the range of 16±4 ppm / K but within the range of 16±8 ppm / K.
[0285] × (poor): The linear expansion coefficient in the in-plane direction is outside the range of 16±8 ppm / K.
[0286] [Table 1]
[0287]
[0288] [Table 2]
[0289]
[0290] As shown in Table 1, when all inorganic fillers have a specific surface area of 30 m 2 / cm 3 In Examples 1 to 8 in which the maximum diameter of the inorganic filler was 100 μm or less and the content of the inorganic filler was 0.1 vol % or more and 60 vol % or less, the resin composition could be formed into a sheet by melt extrusion without causing contamination.
[0291] In the resin compositions of Examples 1 to 8, the melt tension at a temperature 20° C. higher than the melting point of the resin composition was 1.0 mN or more.
[0292] The specific surface area of the inorganic filler in Examples 1 to 8 is 20 m 2 / cm 3 In the resin sheets of Examples 2, 3, 5, 6, 7 and 8 below, the specific surface area ratio of the inorganic filler is 20 m 2 / cm 3Compared with the resin sheets of Example 1 and Example 4, the water absorption rate is lower.
[0293] The resin sheets of Examples 3 and 6, which had a tensile elongation at break of 5% or more and less than 10% among Examples 1 to 8, did not break even when bent 90°. Furthermore, the resin sheets of Examples 1, 2, 4, 5, 7, and 8, which had a tensile elongation at break of 10% or more among Examples 1 to 8, did not break even when bent 180°.
[0294] In the resin sheets of Examples 2, 3, 5 and 6, the linear expansion coefficients in the in-plane direction of which are outside the range of 16±4ppm / K but within the range of 16±8ppm / K, the linear expansion coefficients in the in-plane direction are close to that of copper foil (about 16ppm / K), and therefore, when a resin sheet or a laminated substrate with a conductor layer is formed using the resin sheet or copper foil, warping is unlikely to occur. In addition, in the resin sheets of Examples 1, 4, 7 and 8, the linear expansion coefficients in the in-plane direction of which are within the range of 16±4ppm / K, the linear expansion coefficients in the in-plane direction are close enough to that of copper foil (about 16ppm / K), and therefore, when a resin sheet or a laminated substrate with a conductor layer is formed using the resin sheet or copper foil, warping does not occur.
[0295] On the other hand, as shown in Table 2, when the specific surface area of the inorganic filler is not 30 m 2 / cm 3 In the following Comparative Examples 1 and 4, the resin composition could not be formed into a sheet by the melt extrusion method.
[0296] As shown in Table 2, in Comparative Examples 2 and 5 in which the maximum diameter of the inorganic filler was not 100 μm or less, the resin composition could not be formed into a sheet by the melt extrusion method.
[0297] As shown in Table 2, in Comparative Examples 3 and 6 in which the content of the inorganic filler was not 0.1 vol % or more and 60 vol % or less, the resin composition could not be formed into a sheet by the melt extrusion method.
[0298] As shown in Table 2, in Comparative Example 7, although the resin composition could be formed into a sheet, contamination occurred in the obtained resin sheet.
[0299] As described above, in Comparative Examples 1 to 6, resin sheets could not be produced, and therefore, the water absorption, tensile elongation at break, and linear expansion coefficient in the in-plane direction could not be evaluated. In addition, in Comparative Example 7, there was an influence of contamination, and therefore, the water absorption, tensile elongation at break, and linear expansion coefficient in the in-plane direction were not evaluated.
[0300] This specification discloses the following contents.
[0301] <1>
[0302] A resin composition, characterized in that
[0303] The resin composition comprises a liquid crystal polymer and an inorganic filler.
[0304] The specific surface area of the above inorganic filler is 30m 2 / cm 3 the following,
[0305] The maximum diameter of the inorganic filler is less than 100 μm.
[0306] The content of the inorganic filler is 0.1 vol % or more and 60 vol % or less.
[0307] <2>
[0308] The resin composition according to <1>, wherein
[0309] The specific surface area of the above inorganic filler is 20m 2 / cm 3 the following.
[0310] <3>
[0311] The resin composition according to <1> or <2>, wherein
[0312] The inorganic filler is in a plate shape.
[0313] <4>
[0314] The resin composition according to <3>, wherein
[0315] The average particle size of the inorganic filler is 0.1 μm or more and 30 μm or less.
[0316] The thickness of the inorganic filler is 1 nm or more and 1000 nm or less.
[0317] The inorganic filler has an aspect ratio of 2 or more and 100 or less.
[0318] <5>
[0319] The resin composition according to any one of <1> to <4>, wherein
[0320] The melt tension at a temperature 20° C. higher than the melting point of the resin composition is 1.0 mN or more.
[0321] <6>
[0322] A resin sheet, characterized in that
[0323] The resin sheet includes the resin composition according to any one of <1> to <5>.
[0324] <7>
[0325] A resin sheet with a conductor layer, characterized in that:
[0326] The resin sheet with a conductor layer comprises:
[0327] <6> The resin sheet described in; and
[0328] A conductor layer is adjacent to at least one main surface side of the resin sheet.
[0329] <8>
[0330] A laminate substrate, characterized in that
[0331] This laminated substrate includes the resin sheet with a conductor layer as described in <7>.
[0332] <9>
[0333] A method for manufacturing a resin sheet, characterized in that:
[0334] The method for producing the resin sheet comprises the following steps:
[0335] A resin composition is prepared, the resin composition comprising a liquid crystal polymer and a specific surface area of 30 m 2 / cm 3 An inorganic filler having a maximum diameter of 100 μm or less, wherein the content of the inorganic filler is 0.1 vol% to 60 vol%; and
[0336] The resin composition is formed into a sheet by melt extrusion.
[0337] Description of Reference Numerals
[0338] 1, 1', 1'', 1A, 1B, 1C resin sheet;
[0339] 1a, 1Aa, 1Ba, 1Ca first main surface of the resin sheet;
[0340] 1b, 1Ab, 1Bb, 1Cb second main surface of the resin sheet;
[0341] 1g, 1Ag, 1Bg, 1Cg liquid crystal polymer;
[0342] 1h, 1h'', 1Ah, 1Bh, 1Ch inorganic filler;
[0343] 1s, 1s', 1s'', 1As, 1Bs, 1Cs resin compositions;
[0344] 2. 2A, 2B, 2B', 2B'', 2C conductor layer;
[0345] 3. Surface treatment layer;
[0346] 10, 10A, 10B, 10C resin sheet with conductor layer;
[0347] 20A, 20B, 20C, 20D interlayer connecting conductors;
[0348] 21A, 21B, 21C, 21D vias;
[0349] 22A, 22B, 22C, 22D conductive paste;
[0350] 50 laminated substrate.
Claims
1. A resin composition, characterized in that The resin composition comprises a liquid crystal polymer and an inorganic filler, The specific surface area of the inorganic filler is 30 m 2 / cm 3 the following, The maximum diameter of the inorganic filler is less than 100 μm, The content of the inorganic filler is 0.1 vol % or more and 60 vol % or less.
2. The resin composition according to claim 1, wherein The specific surface area of the inorganic filler is 20 m 2 / cm 3 the following.
3. The resin composition according to claim 1 or 2, wherein The inorganic filler is in plate shape.
4. The resin composition according to claim 3, wherein The average particle size of the inorganic filler is 0.1 μm or more and 30 μm or less. The thickness of the inorganic filler is greater than or equal to 1 nm and less than or equal to 1000 nm. The inorganic filler has an aspect ratio of 2 or more and 100 or less.
5. The resin composition according to any one of claims 1 to 4, wherein The melt tension at a temperature 20° C. higher than the melting point of the resin composition is 1.0 mN or more.
6. A resin sheet, characterized in that: The resin sheet includes the resin composition according to any one of claims 1 to 5.
7. A resin sheet with a conductor layer, characterized in that: The resin sheet with a conductor layer comprises: The resin sheet according to claim 6; and A conductor layer is adjacent to at least one main surface side of the resin sheet.
8. A laminate substrate, characterized in that: The laminated substrate comprises the resin sheet with a conductor layer according to claim 7 .
9. A method for producing a resin sheet, characterized in that: The method for producing the resin sheet comprises the following steps: A resin composition is prepared, the resin composition comprising a liquid crystal polymer and a specific surface area of 30 m 2 / cm 3 An inorganic filler having a maximum diameter of 100 μm or less and a content of 0.1 vol % to 60 vol % or less; and The resin composition is formed into a sheet by melt extrusion.
